Emissivity Calculations Under DCA-UTA Approximation for NLTE Plasmas (Communications in Computational Physics, 2007)
A model is developed to calculate emission spectrum from plasmas in non-local-thermodynamic-equilibrium (NLTE). The populations are obtained with a Collisional Radiative Model and the spectrum is calculated with the Unresolved-Transition-Array (UTA) approximation. The present model is applied to the calculation of emissivity from low-, medium- and high-Z plasmas. The integrated emissivity and thespectra are compared with those calculated by other theoretical models. In generalspeaking, the present results of the mean charge state and emissivity agree well withsome theoretical ones while large differences are found when all the theoretical resultsare included.